The relationship between homocysteine levels and blood pressure variability with early renal injury marker NGAL in patients with H-type hypertension - Xuanhao Lu; Li Guo; Xiulan Sun; Runrun Fan; Xinping Wang; Yanping He (BMC Cardiovascular Disorders)
Abstract Background H-type hypertension (HTH), characterized by hypertension and hyperhomocysteinemia, may accelerate renal injury. Blood pressure variability (BPV) could exacerbate this process, while neutrophil gelatinase-associated lipocalin (NGAL) serves as an early kidney injury marker. Objectives We aimed to determine whether homocysteine (HCY) levels and BPV independently and interactively predict NGAL in patients with H-type hypertension. Methods In this retrospective study 300 participants with H-type hypertension (mean age 60.3 ± 8.1 years; 53.3% male) underwent 24-hour ambulatory blood pressure monitoring to derive BPV (SD of systolic BP), and fasting blood samples to measure HCY and NGAL. Multiple regression models assessed the associations between homocysteine, BPV and NGAL, adjusting for age, sex, body mass index, and estimated glomerular filtration rate. An interaction term (high HCY ≥ 25 µmol/L × BPV-SD) tested effect modification. Results Mean homocysteine, BPV-SD, and NGAL values were 26.5 ± 7.1 µmol/L, 13.1 ± 2.6 mmHg, and 145 ± 60 ng/mL, respectively. HCY and BPV-SD correlated with NGAL (p < 0.001). In adjusted models, HCY (β = 1.4, p = 0.010) and BPV-SD (β = 2.7, p = 0.003) remained significant predictors of higher NGAL. A significant interaction (β = 2.4, p = 0.001) indicated that the effect of BPV on NGAL was greater among those with higher HCY (≥ 25 µmol/L). Conclusions Elevated HCY and BPV contribute to increased NGAL in HTH, and their interaction suggests particular risk for renal injury when both factors remain high. Our study indicated that lowering HCY and stabilizing BPV could be associated with reduce kidney injury, which requires future interventional studies.